Practice and effectiveness evaluation of integrated teaching of life education and hospice & palliative care for undergraduates in a medical college in Shanghai - JING Limei; WANG Jingrong; WANG Hui (Shanghai yufang yixue)
ObjectiveLife education and hospice & palliative care (HPC) involve many aspects of medicine, humanities and education, which is not only an important public health issue, but also an important livelihood issue and education issue widely concerned at home and abroad. This study aims to explore the design and implementation of integrated life education and HPC small-class teaching curriculum for medical students, and to guide students to build correct attitudes towards life education and HPC in terms of knowledge, ability and emotion.MethodsA general course of Life Education and HPC for College Students was set up in a medical college in Shanghai using online and offline teaching models. The practical evaluation system and semi-structured outline were studied and constructed. The teaching effect data were collected by questionnaire survey and semi-structured qualitative interview. The Wilcoxon rank sum test was used to quantitatively analyze the objective teaching effect while the thematic analysis method was used to evaluate the subjective learning effect of students.ResultsThrough the integrated teaching practice, the quantitative analysis found that students’ overall evaluation of the course was higher. Learning effectiveness and course satisfaction ratings were both higher online than offline (both P<0.01). The qualitative analysis obtained three major themes: the understanding of life and HPC, the development prospect of HPC and its impact on the future life and career, and eight corresponding sub-themes: the value of life, the significance of HPC, human kindness, the promotion of HPC concept, the improvement of HPC services, the acceptance of HPC, the sense of responsibility as medical students, and the enrichment of life experience.ConclusionThe integrated course of life education and HPC for medical students in a medical college in Shanghai has achieved the teaching goals in terms of knowledge, ability and emotion. The study suggests that the integrated teaching model should be further improved by combining the advantages of online and offline teaching, and the construction of a professional curriculum system should be accelerated, so as to include life education and HPC into the required general courses for undergraduates in medical colleges to help students establish a correct outlook on life and values, establish the concept and will of HPC service, and guide the professional quality improvement and career development of future medical career.